A cross-sectional study on gender-based violence among adolescents attending government colleges in urban area of Tirupati, Andhra Pradesh - S., Priyadharshini; R., Sowmya Pallavi; T., Siva Kala; J., Pavan Kumari; G., Ravi Prabhu (International Journal Of Community Medicine And Public Health, 2022)
Background: Gender-based violence (GBV) is one of the most prevalent forms of human rights violations in the world. Across the globe, women and girls-especially adolescents-face the greatest risk. Age-stratified GBV data on adolescents is lacking in India. Approximately 1 in 3 women worldwide may experience physical or sexual violence in her lifetime. In this background the present study was conducted to find out prevalence of GBV among college going adolescents in urban area of Tirupati. Methods: A cross-sectional study was conducted among college going adolescents aged 16-19 years in four government colleges in urban area of Tirupati, Andhra Pradesh from November 2021 to December 2021. Details on socio demographic characteristics and history related to GBV were collected by personal interview using a pretested, semi-structured questionnaire. Descriptive data was summarized in percentages and Chi-square test was used to test the association. Results: A total of 263 students participated in the study with mean age of 18.15±1.01 years, majority being females (54%). About 36.5% faced at least one form of GBV so far. The most common form of violence faced by study subjects was physical (28.1%) followed by psychological violence (17.5%). Physical, sexual and psychological violence was found to be 17.8%, 1.9%, 11.0% in females and 10.3%, 0.7%, 6.5% among males respectively. Conclusion: The present study shows that both male and female are victims of GBV but little higher prevalence was found in females.